The use of artificial intelligence to improve grammar in the english language. - Limones Ríos, Alfredo Renato (Machala: Universidad Técnica de Machala, 2024)
The thesis The Use of Artificial Intelligence to Improve English Grammar among Third-Year High School Students at Colegio Juana de Dios investigates the efficacy of an innovative system based on artificial intelligence AI consisting of seven specific activities for learning and improving English grammar, applied to 47 students. Focusing on the relationship between the implementation of AI tools and grammatical progress in English, the study highlights AI's capability to personalize learning, adapting to the individual needs and paces of each student, which is crucial for overcoming specific challenges in grammar learning. The research is oriented towards a quantitative paradigm with an experimental design, as it aims to demonstrate the improvement in students' grammatical skills following the intervention with the AI-based system. Moreover, by testing the hypothesis through the collection of statistical data and understanding the effects of applying the variables, the system of activities proves that the use of AI tools, through interactive and adaptive activities, can offer a more engaging and effective learning experience, encouraging students to actively participate in their learning process. This approach not only improves grammar but also fosters a positive attitude towards language learning, which can have long-lasting implications on their future linguistic competence.
La Tesis El Uso de la Inteligencia Artificial para Mejorar la Gramática del Idioma Inglés en los Estudiantes de Tercer Año de Bachillerato del Colegio Juana de Dios investiga la eficacia de un innovador sistema basado en inteligencia artificial IA compuesto por siete actividades específicas para el aprendizaje y mejora de la gramática del idioma inglés que fue aplicada a 47 estudiantes. Centrándose en la relación entre la implementación de herramientas de IA y el progreso gramatical en inglés, el estudio destaca la capacidad de la IA para personalizar el aprendizaje, adaptándose a las necesidades y ritmos individuales de cada estudiante, lo cual es fundamental para superar desafíos específicos en el aprendizaje de la gramática. La investigación está orientada hacia el paradigma cuantitativo con un diseño experimental, puesto que pretende demostrar la mejora en las habilidades gramaticales de los estudiantes tras la intervención con el sistema basado en IA. Además, al probar la hipótesis planteada mediante la recolección de datos estadísticos y conocer los efectos en la aplicación de las variables, mediante el sistema de actividades se demuestra que el uso de las herramientas de IA, a través de actividades interactivas y adaptativas, pueden ofrecer una experiencia de aprendizaje más atractiva y efectiva, incentivando a los estudiantes a participar activamente en su proceso de aprendizaje. Este enfoque no solo mejora la gramática, sino que también fomenta una actitud positiva hacia el aprendizaje del idioma, lo que puede tener implicaciones duraderas en su competencia lingüística futura.
Keywords: INTELIGENCIA ARTIFICIAL; ESTUDIANTE; REGLA; GRAMATICA